2002
DOI: 10.1034/j.1600-0447.2002.1o421.x
|View full text |Cite
|
Sign up to set email alerts
|

Could the hypofrontality pattern in schizophrenia be modified through neuropsychological rehabilitation?

Abstract: Cognitive improvements after neuropsychological treatment would possibly be related with the diminution of the functional hypoactivity in the prefrontal areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…Only a minority seem to be amenable to change by specific treatment interventions normally provided by psychiatrists. Better identification and treatment of depression and general psychopathology symptoms such as social anxiety and cognitive problems (Penades et al, 2002) might potentially improve subjective QOL in people with schizophrenia. Family contact was significantly associated with higher subjective QOL and better family support might improve family understanding and functioning and thus the amount of contact after the onset of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…Only a minority seem to be amenable to change by specific treatment interventions normally provided by psychiatrists. Better identification and treatment of depression and general psychopathology symptoms such as social anxiety and cognitive problems (Penades et al, 2002) might potentially improve subjective QOL in people with schizophrenia. Family contact was significantly associated with higher subjective QOL and better family support might improve family understanding and functioning and thus the amount of contact after the onset of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…Still, while such exercises are often rooted in neuropsychology, the links between the exercises and change in neurobiological parameters are often not tested explicitly. Recently, Penades et al (2002) found improved performance on tasks known to assess prefrontal function as well as decreased hypofrontality on SPECT scanning following training on tasks that require prefrontal activity in individuals with schizophrenia. Such ''neurocognitive rehabilitation'' exercises have also been proposed and used for treatment of other conditions associated with prefrontal dysfunction such as addiction disorders (Allen, Goldstein, & Seaton, 1997;Cunha & Novaes, 2004).…”
Section: Cognitive Training Exercisesmentioning
confidence: 98%
“…In some patients a kind of "normalisation" of neuronal responses was assessed [82]. Altogether, the effects were small and inconsistent (see also [83]). Fig.…”
Section: Cognitive Rehabilitation Trainingmentioning
confidence: 99%